Object-oriented analysis and simulation - Hill, David R. C. (Addison-Wesley, 1996)
This book is the first to bring together the techniques of object modelling, advanced software engineering and simulation modelling in a comprehensive guide for students and professionals. By offering an introduction to simulation and state-of-the-art object model concepts, it enables readers to master modelling techniques which meet the challenges inherent in the design and utilization of complex software systems. Following an extensive study of the major object-oriented analysis and design techniques, David Hill shows how a modelling method adapted to simulation can be translated to industrial and research applications. It illustrates how to generate automatic simulation code for the simulation and animation of manufacturing systems, and thus is the only text to provide object-oriented code generation techniques and present the design of a simulation animation builder. Finally, the book includes detailed appendices on simulation languages and an introduction to the C++ programming language.